Use of 18S, 16S rDNA and cytochrome c oxidase sequences in earthworm taxonomy (Oligochaeta, Lumbricidae): the 7th international symposium on earthworm ecology, Cardiff, Wales, 2002 - Pop, Adriana Antonia; Wink, Michael; Pop, Victor V. (Pedobiologia, 2004)
Molecular methods are expected to provide new and more precise means in delimiting genera as well as in establishing phylogenetic relationships among earthworm species. A multigene attempt aiming to evaluate the diagnostic value of the different genes is presented. Complete sequences for nucleic 18S rDNA of 3 earthworm species, partial sequences for ribosomal 16S rDNA of 18 species and 1 subspecies and subunit one for mitochondrial cytochrome c oxidase (COI) for 19 taxa were obtained. Nucleotide sequences of genes were used to reconstruct molecular phylogeny with maximum parsimony. These molecular data are considered as complementary diagnostic characters partially fitting the traditional species grouping into different taxonomic systems.
Gesehen am 04.10.2017
Keywords: Konferenzschrift